Forensic medical examination after sexual violence: implications based on victims’ perceptions - Berger, Laura; Tuschy, Benjamin; Stefanovic, Stefan; Yen, Kathrin; Weiß, Christel; Sütterlin, Marc; Spaich, Saskia; Berlit, Sebastian (In vivo, 2023)
Background/Aim: The objective of this study was to assess the perception of the forensic medical examination (FME) by victims of sexual violence. Based on patient-related outcomes gained in terms of personnel, chronological and spatial parameters, an additional aim was to derive improved examination procedures. Patients and Methods: A total of 49 sexually assaulted women were enrolled in this study. After standardized FME by a forensic doctor followed by a gynecologist, women were asked to complete a questionnaire addressing general perception, preferences regarding attending staff’s sex, sequence and time frame of the examinations performed. The attending gynecologist also completed a questionnaire addressing demographic and medical parameters of the patient as well as assault-related information. Results: The examination setting in general was evaluated positively. Nevertheless, 52% of examined victims perceived the FME as an additional psychological burden. Overall, 85% of the affected women preferred a female forensic physician and 76% a female gynecologist to perform the examination. When women said they experienced a violation of their privacy during the gynecological examination, a male was more often present (60% vs. 35%, p=0.0866). Regarding the sequence of the examination components, 65% of the victims preferred to start with their medical history followed by the forensic and then the gynecological examination. Conclusion: Forensic medical and gynecological examination after sexual assault is an essential procedure, yet it is a potentially further traumatizing experience for the victim. The identified patient preferences should be taken into account in order to diminish further trauma.